Production and characterisation of activated carbons made from coffee industry residues - Valente Nabais, Joao (2006)
Porous materials are usually heterogeneous both structurally and energetically. Activated carbon fibres (ACFs) are relatively novel fibrous adsorbents produced for example from pith, cellulose, lignocellulose, phenol resin and polyacrylonityile (Peebles, 1995; Ryu, 1999). ACFs show important advantages with respect to conventional activated carbons. Among these advantages it is worth noting their high adsorption capacity and easiness to handle. Their main inconvenience lays on the difficulty of choosing adequate activating agents and activation conditions that are required in order to maintain the fibrous morphology. The adsorption capacity of ACFs depends on many factors, such as raw materials, activation process, pore structure and surface functionalities (Suffet, 1981; Park, 1999). Surface roughness is an important factor that influences the adsorption properties of an activated carbon. Fractal dimension is a measure of roughness of a surface. The use of the fractal concept is becoming very popular as a tool to characterize the texture of complex materials, such as porous solids. The fractal properties of these porous systems were determined by means of several techniques such as gas adsorption, mercury porosimetry and Small-Angle X-Ray Scattering (SAXS and SANS). Kenaf is an herbaceous annual plant that belongs to the family of Malvaceae. Kenaf possesses both, long and short fibre. The aim of this work is to study the influence of the preparation conditions on the fractal dimension and porous texture of ACFs prepared from long fibres of kenaf by physical activation using carbon dioxide as activating agent. * Author